2002
DOI: 10.1038/sj.onc.1205174
|View full text |Cite
|
Sign up to set email alerts
|

LATS1 tumor suppressor regulates G2/M transition and apoptosis

Abstract: The LATS1 gene is a mammalian member of the novel lats tumor suppressor family. Both lats mosaic¯ies and LATS1 de®cient mice spontaneously develop tumors. Our previous studies have shown that inactivation of Drosophila lats leads to up-regulation of cyclin A in thē y, and the human LATS1 protein associates with CDC2 in early mitosis in HeLa cells, suggesting that the lats gene family may negatively regulate cell proliferation by modulating CDC2/Cyclin A activity. We demonstrate here that transduction of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 35 publications
7
138
2
1
Order By: Relevance
“…In contrast, LATS1/2 kinases, which can also signal downstream of MST1/2 [13,14,83], have been shown to play a role in later stages of mitosis. A decade ago, it was reported that LATS1 can inhibit CDK1 activity in mitosis, thereby influencing G2/M cell cycle progression [25,84]. Analysis of cells overexpressing LATS1 supported a role for LATS1 in mitosis, since LATS1 overexpression resulted in a G2/M cell cycle arrest [84][85][86].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, LATS1/2 kinases, which can also signal downstream of MST1/2 [13,14,83], have been shown to play a role in later stages of mitosis. A decade ago, it was reported that LATS1 can inhibit CDK1 activity in mitosis, thereby influencing G2/M cell cycle progression [25,84]. Analysis of cells overexpressing LATS1 supported a role for LATS1 in mitosis, since LATS1 overexpression resulted in a G2/M cell cycle arrest [84][85][86].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 97%
“…A decade ago, it was reported that LATS1 can inhibit CDK1 activity in mitosis, thereby influencing G2/M cell cycle progression [25,84]. Analysis of cells overexpressing LATS1 supported a role for LATS1 in mitosis, since LATS1 overexpression resulted in a G2/M cell cycle arrest [84][85][86]. Subsequent studies further supported the view that LATS1 is a regulator of mitosis by showing that LATS1 associates with the AMR and midbody in cytokinesis [87], that LATS1 co-localises with Zyxin at the mitotic spindle apparatus [88], that LATS1 can interact with LIMK1 in mitosis, a key regulator of the actin polymerisation machinery [87], and that endogenous human LATS1 plays a role in mitosis [89].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…Both LATS proteins participate in a wide variety of cellular processes. LATS1 suppresses cell growth through inducing cell cycle arrest at the G 2 /M phase by interrupting the Cdc2/Cyclin B complex thereby inhibiting cell proliferation [24,25]. Additionally, LATS1 negatively regulates cytoskeleton protein LIMK1.…”
Section: Large Tumor Suppressor (Lats)/nuclear Dbf2-related (Ndr) Genmentioning
confidence: 99%
“…34 Beside their roles within the Hippo pathway, Lats1/2 may regulate cell cycle progression and apoptosis. [35][36][37][38] Lats1 has been shown to regulate both mitotic exit 39 and cytokinesis 40 and to play a role in cellular senescence, since reduction of Lats1 levels is, at least partly, responsible for cytokinetic block in senescent cells. 41 Lats2 has also been found to protect p53 from Mdm2-mediated degradation while p53 stimulates Lats2 expression.…”
Section: Mst1/2mentioning
confidence: 99%
“…49 In vitro, overexpression of Lats1 or Lats2 is sufficient to suppress ephithelial-messenchymal transition and tumor growth of cancer cells while their downregulation result in cell overgrowth and transformation. 32,35,36,44,45,50 …”
Section: Mst1/2mentioning
confidence: 99%